2019
DOI: 10.3390/md17070430
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of Benzo[d]Thiazol-2(3H)-One Derivatives and Their Antidepressant and Anticonvulsant Effects

Abstract: Thirty-four new benzo[d]thiazol derivatives 2a–2i, 3a–3r, and 4a–4g were synthesized and investigated for their potential antidepressant and anticonvulsant effects. In a forced swimming test, 2c and 2d showed the highest antidepressant and anticonvulsant effects. 2c and 2d displayed a higher percentage decrease in immobility duration (89.96% and 89.62%, respectively) than that of fluoxetine (83.62%). In the maximal electroshock seizure test, 3n and 3q showed the highest anticonvulsant effect, with ED50 values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…The 1 H and 13 C NMR spectra were recorded on a Bruker AVANCE III (400 MHz) spectrometer in DMSO-d6. As an internal standard, chemical shifts are expressed in δppm downfield from Tetramethylsilane (TMS).…”
Section: Experimental Section: Materials and Methodsmentioning
confidence: 99%
“…The 1 H and 13 C NMR spectra were recorded on a Bruker AVANCE III (400 MHz) spectrometer in DMSO-d6. As an internal standard, chemical shifts are expressed in δppm downfield from Tetramethylsilane (TMS).…”
Section: Experimental Section: Materials and Methodsmentioning
confidence: 99%
“…Thiazole, a five-membered ring system carrying three carbons, one nitrogen, and one sulfur atom, is one such structure. It has been reported that thiazole-bearing compounds have some central nervous system (CNS)-related effects, such as anti-schizophrenic [4], anti-parkinsonian [5], neuroprotective [6], acetylcholinesterase inhibitory [7], anticonvulsant [8], antidepressant [9], and sedative-hypnotic [10] effects. Another heterocyclic structure, piperazine, is a 6-membered saturated ring system containing two nitrogen atoms in the first and fourth positions.…”
Section: Introductionmentioning
confidence: 99%
“…Its aromaticity makes it relatively stable, although as a heterocyclic, it has reactive sites which allow for functionalization8. Benzoxazole displays diverse pharmacological properties including antimicrobial [9][10][11][12][13][14] , multidrug resistant cancer cell activities [15][16] , antiinflammatory [17][18][19] , anticonvulsant 20 , antidepressant 21 , anti-HIV [22][23] , Antihypertensive 24 , anthelmintic 25 activities.…”
Section: Introductionmentioning
confidence: 99%